Revised nomenclature and classification of inherited ichthyoses: results of the first ichthyosis consensus conference in Sorèze 2009 - Oji, Vinzenz; Tadini, Gianluca; Akiyama, Masashi; Blanchet Bardon, Claudine; Bodemer, Christine; Bourrat, Emmanuelle; Coudiere, Philippe; DiGiovanna, John J.; Elias, Peter; Fischer, Judith; Fleckman, Philip; Gina, Michal; et al. (Journal of the American Academy of Dermatology, 2010)
Background - Inherited ichthyoses belong to a large, clinically and etiologically heterogeneous group of mendelian disorders of cornification, typically involving the entire integument. Over the recent years, much progress has been made defining their molecular causes. However, there is no internationally accepted classification and terminology. - Objective - We sought to establish a consensus for the nomenclature and classification of inherited ichthyoses. - Methods - The classification project started at the First World Conference on Ichthyosis in 2007. A large international network of expert clinicians, skin pathologists, and geneticists entertained an interactive dialogue over 2 years, eventually leading to the First Ichthyosis Consensus Conference held in Sorèze, France, on January 23 and 24, 2009, where subcommittees on different issues proposed terminology that was debated until consensus was reached. - Results - It was agreed that currently the nosology should remain clinically based. “Syndromic” versus “nonsyndromic” forms provide a useful major subdivision. Several clinical terms and controversial disease names have been redefined: eg, the group caused by keratin mutations is referred to by the umbrella term, “keratinopathic ichthyosis”-under which are included epidermolytic ichthyosis, superficial epidermolytic ichthyosis, and ichthyosis Curth-Macklin. “Autosomal recessive congenital ichthyosis” is proposed as an umbrella term for the harlequin ichthyosis, lamellar ichthyosis, and the congenital ichthyosiform erythroderma group. - Limitations - As more becomes known about these diseases in the future, modifications will be needed. - Conclusion - We have achieved an international consensus for the classification of inherited ichthyosis that should be useful for all clinicians and can serve as reference point for future research.